Social innovation and social entrepreneurship: discovering origins, exploring current and future trends - Farinha, Luís (2020)
Nonprofit sector integrates an important part of the economy, which serves as a critical factor for social change. Social innovation and social entrepreneurship are of paramount importance for the nonprofit sector aiming to solve social needs. The purpose of this paper is, through bibliometric mapping techniques, based on 2695 documents, to understand thematic evolution of social innovation and social entrepreneurship. The main conclusion is that, from the analysis, we can see that the scientific production in this field of knowledge has intensified in recent years, but the centrality and the search density undergo major changes. New paths for future research are outlined.